2022
DOI: 10.3390/v14020199
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ribonucleoprotein A1 (hnRNPA1) Interacts with the Nucleoprotein of the Influenza a Virus and Impedes Virus Replication

Abstract: Influenza A virus (IAV), like other viruses, depends on the host cellular machinery for replication and production of progeny. The relationship between a virus and a host is complex, shaped by many spatial and temporal interactions between viral and host proteome, ultimately dictating disease outcome. Therefore, it is imperative to identify host-virus interactions as crucial determinants of disease pathogenies. Heterogeneous ribonucleoprotein A1 (hnRNPA1) is an RNA binding protein involved in the life cycle of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…hnRNP A1 interacts with p17 protein of avian reovirus (ARV) to facilities its nuclear import and export (218). hnRNP A1 also interacts with nucleoprotein (NP) of IAV and co-localize in both nucleus and mitochondria of mammalian cells that are either transfected with NP or infected with IAV (219). Similarly, hnRNP A1 interacts with nucleocapsid (N) protein of porcine epidemic diarrhea virus (PEDV) and enhances the PEDV infection (220).…”
Section: Hnrnps Interact With Viral Proteins To Control Viral Replica...mentioning
confidence: 99%
See 1 more Smart Citation
“…hnRNP A1 interacts with p17 protein of avian reovirus (ARV) to facilities its nuclear import and export (218). hnRNP A1 also interacts with nucleoprotein (NP) of IAV and co-localize in both nucleus and mitochondria of mammalian cells that are either transfected with NP or infected with IAV (219). Similarly, hnRNP A1 interacts with nucleocapsid (N) protein of porcine epidemic diarrhea virus (PEDV) and enhances the PEDV infection (220).…”
Section: Hnrnps Interact With Viral Proteins To Control Viral Replica...mentioning
confidence: 99%
“…The discovery of novel therapeutic options against important human and animal viral pathogens can be advanced by understanding how cellular RBPs, including hnRNPs, regulate virus infection (49). For example, in addition to acting as a host-protective mechanism, hnRNP A1 may also hold potential as an antiviral target to develop therapy for human rhinovirus (HRV) and IAV (157,158,219). Similarly, hnRNP E2 has the inhibitory effects on VSV replication (240).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…hnRNPA1 binds with viral RNA and viral polymerase NS5B to inhibit hepatitis C virus replication [ 13 , 14 ]. Besides, hnRNPA1 interacts with NP of influenza A virus and inhibits viral replication [ 15 ]. On the other hand, it acts as a pro-viral factor.…”
Section: Introductionmentioning
confidence: 99%
“…hnRNP-C is implicated in numerous viral infections, including poliovirus, hepatitis delta virus, Ebola virus, dengue virus, the human papillomavirus type 16, MERS-CoV, and SARS-CoV-2 [ 16 , 17 , 18 , 19 , 20 ]. Recently, influenza NP was shown to interact with hnRNP-A2/B1, hnRNP-AB, and hnRNP-A1, which are also members of the family of more than 20 hnRNPs [ 21 , 22 , 23 ], while hnRNP-C was suggested to interact with influenza NS1 [ 24 ]. NP was found to interact with the glycine-rich domain of hnRNP-A2/B1, which was shown to be a positive regulator of RNP activity [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, viral replication is repressed. Kaur et al then demonstrated that hnRNP-A1 interacts with NP so that it negatively regulates the NP expression level and viral growth via an unknown pathway [ 23 ]. Hence, the binding of different hnRNPs to NP may lead to either up- or downregulation of RNP activity.…”
Section: Introductionmentioning
confidence: 99%